To solve this system of equations, we can use the method of elimination.
Multiply the second equation by 3:
3(3x - 5y) = 3(5)
9x - 15y = 15
Now we can add this new equation to the first equation to eliminate the x variable:
-3x - 4y + 9x - 15y = -23 + 15
6x - 19y = -8
Now, we need to solve for y by rearranging the equation:
19y = 6x + 8
y = (6x + 8)/19
Now, substitute y back into one of the original equations (let's use the first one) to solve for x:
-3x - 4(6x + 8)/19 = -23
-3x - (24x + 32)/19 = -23
-57x - 24x - 32 = -437
-81x = -405
x = 5
Now we can substitute x = 5 back into y = (6x + 8)/19 to solve for y:
y = (6(5) + 8)/19
y = (30 + 8)/19
y = 38/19
y = 2
Therefore, the solution to the system of equations is x = 5 and y = 2.
solve the system of two linear equations
-3x -4y=-23
3x-5y=5
1 answer